The molecular detection of leishmaniasis agent in Dhi-Qar Province patients - Amer Saadi Mohammed/ Ali Hafedh Abbas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Objective: One of the most common parasitic diseases is cutaneous leishmaniasis, which is seen especially in the Middle East and North Africa and in the Old World. Female sand flies carry the disease. Visitors, immigrants, and military members are infected with these flies every year.